PENGGUNAAN VIDEO UNTUK MENINGKATKAN HAPALAN DOA ANAK USIA DINI - Muchamad Arif; Rosyidatun Nafisah (Universitas Narotama, 2021)
This research aimed to determine the success of using video to improve early childhood prayer memorization at the Pos Paud Terpadu Bintang. The videos were animated videos of Islamic children who were familiar with children. The method was descriptive qualitative. It conducted for three meetings. The research subjects were 20 students, consisting of 12 girls and 8 boys. The learning media needed besides video were projector, laptop and speaker. The results showed that the children were very enthusiastic in learning. They were interested in the video so that the teacher could repeat the activities or prayers that had been shown in the video with fun. Then, the children easily memorized the prayers by imitating the prayers repeated by the teacher based on the videos the children had watched. Keywords: video, memorize, pray, early childhood